Negative electrode active material layer, negative electrode, and lithium ion secondary battery
By introducing fibrous substances as a skeleton into the negative electrode active material layer, the volume expansion problem of the negative electrode active material during charging is solved, and the charge and discharge characteristics and cycle stability of the lithium-ion secondary battery are improved.
Patent Information
- Application Number
- CN202280095040.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-15
- Publication Date
- 2024-12-13
AI Technical Summary
The volume expansion of the negative electrode active substance during charging leads to a decrease in the circulation characteristics of the lithium-ion secondary battery, cutting of the conductive paths and peeling of the solid electrolyte interface, which affects the charging and discharging characteristics of the battery.
The fiber-like substances are introduced into the negative electrode active material layer, such as titanium oxide, potassium titanate, aluminum oxide, etc., and the fiber length is more than 20 μm and less than 150 μm. The fiber-like substances act as the skeleton of the negative electrode active material layer to control the average particle between the negative electrode active material Distance and layer thickness to suppress expansion and cracking.
It effectively prevents cracking of the negative electrode active material layer during charging and discharging, maintains conductive channels, improves the charge and discharge characteristics of lithium-ion secondary batteries and does not deteriorate easily, and extends battery life.
Smart Images

Figure CN119137769A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a negative electrode active material layer, a negative electrode and a lithium ion secondary battery. Background Art
[0002] Lithium-ion secondary batteries are widely used as power sources for mobile devices such as mobile phones and notebook computers, hybrid vehicles, and the like.
[0003] The charging and discharging of lithium-ion secondary batteries is performed by an active material layer containing active materials. In order to improve the characteristics of lithium-ion secondary batteries, the structure within the active material layer is being studied.
[0004] For example, Patent Documents 1 and 2 describe active material layers containing fillers of a predetermined shape. For example, Patent Documents 3 and 4 describe the use of two types of lithium cobalt oxides having different tap densities as active materials. For example, Patent Document 5 describes an active material layer in which carbon nanofibers are added to a binder. For example, Patent Document 6 describes an active material layer in which fibrous carbon is added to a binder. Prior art literature Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2006-172901 Patent Document 2: Japanese Patent Application Publication No. 2019-186164 Patent Document 3: U.S. Patent Application Publication No. 2005 / 0271576 Patent Document 4: U.S. Patent Application Publication No. 2008 / 0087862 Patent Document 5: U.S. Patent Application Publication No. 2007 / 0092796 Patent Document 6: U.S. Patent Application Publication No. 2011 / 0266495 Summary of the invention Technical problem to be solved by the invention
[0006] The negative electrode active material containing silicon undergoes a large volume expansion during charging. The volume expansion of the negative electrode active material causes a decrease in the cycle characteristics of the battery. When the volume expansion of the negative electrode active material occurs, for example, the conductive path between the negative electrode active materials is cut off, peeling occurs at the interface between the negative electrode active material layer and the collector, cracks are generated in the SEI (Solid Electrolyte Interphase) film, and decomposition of the electrolyte occurs. These situations will reduce the cycle characteristics of the battery. Even when a silicon-based material is used as the negative electrode active material, a battery whose charge and discharge characteristics are not easily deteriorated is required.
[0007] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a negative electrode active material layer, a negative electrode, and a lithium ion secondary battery in which charge and discharge characteristics are less likely to deteriorate. Technical means for solving technical problems
[0008] In order to solve the above technical problems, the following technical means are provided.
[0009] (1) The negative electrode active material layer of the first embodiment comprises a negative electrode active material and a fibrous material. The negative electrode active material comprises silicon. The fibrous material comprises one or more selected from titanium oxide, potassium titanate, aluminum oxide, silicon carbide, silicon nitride and silicon oxide. The fiber length of the fibrous material is not less than 20 μm and not more than 150 μm. The value obtained by dividing the layer thickness of the negative electrode active material layer by the fiber length is not less than 0.4 and not more than 1.0.
[0010] (2) In the negative electrode active material layer of the above embodiment, the average distance between particles of the negative electrode active material may be 3.0 μm or more and 4.5 μm or less.
[0011] (3) In the negative electrode active material layer of the above embodiment, the fibrous material may include one or more selected from the group consisting of titanium oxide, potassium titanate, and aluminum oxide.
[0012] (4) The negative electrode of the second embodiment includes the negative electrode active material layer of the above embodiment.
[0013] (5) A lithium ion secondary battery according to a third aspect comprises: the negative electrode according to the above aspect; a positive electrode facing the negative electrode; and an electrolyte connecting the negative electrode and the positive electrode. Effects of the Invention
[0014] The negative electrode active material layer, the negative electrode, and the charge and discharge characteristics of the lithium ion secondary battery of the above-described embodiment are unlikely to deteriorate. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is a schematic cross-sectional view of the lithium ion secondary battery according to the first embodiment. Figure 2 It is an enlarged schematic diagram of a characteristic portion of the negative electrode active material layer of the first embodiment. DETAILED DESCRIPTION
[0016] Hereinafter, the embodiments will be described in detail with reference to the accompanying drawings as appropriate. In the drawings used in the following description, there are cases where the features are enlarged to make the features easier to understand, and the dimensional ratios of the various structural elements are sometimes different from the actual structure. The materials, dimensions, etc. illustrated in the following description are only examples and are not intended to limit the present invention. They can be appropriately changed and implemented without changing the gist of the present invention.
[0017] [Lithium-ion secondary battery] Figure 1 It is a schematic diagram of the lithium ion secondary battery of the first embodiment. Figure 1 The lithium-ion secondary battery 100 shown in the figure includes a power generation element 40, an outer casing 50, and an electrolyte (e.g., a non-aqueous electrolyte). The outer casing 50 covers the periphery of the power generation element 40. The power generation element 40 is connected to the outside via a pair of terminals 60 and 62. The non-aqueous electrolyte is contained in the outer casing 50. Figure 1 Although the case where one power generating element 40 is included in the exterior body 50 is illustrated in FIG. 1 , a plurality of power generating elements 40 may be stacked.
[0018] (Power generation element) The power-generating element 40 includes a separator 10, a positive electrode 20, and a negative electrode 30. The power-generating element 40 may be a stacked body in which these are stacked, or a wound body in which a stacked structure is wound.
[0019] <Positive electrode> The positive electrode 20 includes, for example, a positive electrode current collector 22 and a positive electrode active material layer 24 . The positive electrode active material layer 24 is in contact with at least one surface of the positive electrode current collector 22 .
[0020] [Positive electrode collector] The positive electrode current collector 22 is, for example, a conductive plate. The positive electrode current collector 22 is, for example, a thin metal plate of aluminum, copper, nickel, titanium, stainless steel, etc. Lightweight aluminum is suitable for the positive electrode current collector 22. The average thickness of the positive electrode current collector 22 is, for example, not less than 10 μm and not more than 30 μm.
[0021] [Positive electrode active material layer] The positive electrode active material layer 24 contains, for example, a positive electrode active material, and may contain a conductive auxiliary agent and a binder as necessary.
[0022] The positive electrode active material includes an electrode active material that can reversibly perform absorption and release of lithium ions, extraction and insertion (intercalation) of lithium ions, or doping and dedoping of lithium ions and counter anions.
[0023] The positive electrode active material is, for example, a composite metal oxide. Composite metal oxides include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), lithium manganese spinel (LiMn2O4), and LiNiO2. x Co y Mn z M aO2 compounds (in the general formula, x+y+z+a=1, 0≤x<1, 0≤y<1, 0≤z<1, 0≤a<1, M is one or more elements selected from Al, Mg, Nb, Ti, Cu, Zn, Cr), lithium vanadium compounds (LiV2O5), olivine-type LiMPO4 (wherein M represents one or more elements selected from Co, Ni, Mn, Fe, Mg, Nb, Ti, Al, Zr or VO), lithium titanate (Li4Ti5O 12 )、LiNi x Co y Al z O2 (0.9<x+y+z<1.1). The positive electrode active material may also be an organic substance. For example, the positive electrode active material may be polyacetylene, polyaniline, polypyrrole, polythiophene, or polyacene.
[0024] The positive electrode active material may also be a material that does not contain lithium. Examples of materials that do not contain lithium include FeF3, conjugated polymers containing organic conductive substances, Chevrel Phase compounds, transition metal chalcogenides, vanadium oxides, niobium oxides, and the like. For materials that do not contain lithium, any one material may be used alone, or a combination of multiple materials may be used. In the case where the positive electrode active material is a material that does not contain lithium, for example, discharge is initially performed. By discharging, lithium is embedded in the positive electrode active material. In addition, in the case where the positive electrode active material is a material that does not contain lithium, lithium may also be pre-doped chemically or electrochemically.
[0025] The conductive additive improves the electronic conductivity between the positive electrode active materials. The conductive additive is, for example, carbon powder, carbon nanotubes, carbon materials, metal powder, a mixture of carbon materials and metal powder, and conductive oxides. Carbon powder is, for example, carbon black, acetylene black, Ketjen black, etc. Metal powder is, for example, powder of copper, nickel, stainless steel, iron, etc.
[0026] There is no particular limitation on the content of the conductive additive in the positive electrode active material layer 24. For example, the content of the conductive additive is 0.5 mass % to 20 mass %, preferably 1 mass % to 5 mass %, based on the total mass of the positive electrode active material, the conductive additive, and the binder.
[0027] The binder in the positive electrode active material layer 24 binds the positive electrode active materials to each other. As for the binder, a well-known binder can be used. As for the binder, it is preferred to use a binder that is insoluble in the electrolyte and has oxidation resistance and adhesiveness. The binder is, for example, a fluororesin. The binder is, for example, polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polytetrafluoroethylene (PTFE), polyamide (PA), polyimide (PI), polyamideimide (PAI), polybenzimidazole (PBI), polyether sulfone (PES), polyacrylic acid and its copolymers, metal ion crosslinked bodies of polyacrylic acid and its copolymers, polypropylene (PP) or polyethylene (PE) obtained by grafting maleic anhydride, and mixtures thereof. The binder for the positive electrode active material layer is particularly preferably PVDF.
[0028] There is no particular limitation on the content of the binder in the positive electrode active material layer 24. For example, relative to the total mass of the positive electrode active material, the conductive aid, and the binder, the content of the binder is 1% by mass or more and 15% by mass or less, preferably 1.5% by mass or more and 5% by mass or less. When the content of the binder is small, the bonding strength of the positive electrode 20 becomes weak. When the content of the binder is high, because the electrochemical property of the binder is inactive, it does not contribute to the discharge capacity, and therefore, the energy density of the lithium ion secondary battery 100 is reduced.
[0029] <Negative electrode> The negative electrode 30 includes, for example, a negative electrode current collector 32 and a negative electrode active material layer 34 . The negative electrode active material layer 34 is formed on at least one surface of the negative electrode current collector 32 .
[0030] [Negative electrode current collector] The negative electrode current collector 32 is, for example, a conductive plate material. The negative electrode current collector 32 can be made of the same material as the positive electrode current collector 22 .
[0031] [Negative Electrode Active Material Layer] Figure 2 Schematic diagram of an enlarged characteristic portion of the negative electrode active material layer 34. The negative electrode active material layer 34 includes, for example, a negative electrode active material 1, a fibrous material 2, a conductive aid 3, and a binder (not shown). The negative electrode active material layer 34 may also include other substances such as a dispersion stabilizer.
[0032] The negative electrode active material 1 contains silicon. The negative electrode active material 1 may be any of simple silicon, silicon alloy, silicon compound, and silicon composite. The negative electrode active material 1 may be crystalline or amorphous.
[0033] Silicon alloys such as X nSi represents. X is a cation. For example, X is Ba, Mg, Al, Zn, Sn, Ca, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ge, Y, Zr, Nb, Mo, W, Au, Ti, Na, K, etc. n satisfies 0≤n≤0.5.
[0034] Silicon compounds such as SiO x denoted by silicon oxide. x satisfies, for example, 0.8≤x≤2. Silicon oxide may consist of only SiO2, may consist of only SiO, or may be a mixture of SiO and SiO2. In addition, silicon oxide may lack a portion of oxygen.
[0035] Silicon composites are, for example, materials in which at least a portion of the surface of particles of silicon or silicon compounds is covered with a conductive material. Conductive materials are, for example, carbon materials, Al, Ti, Fe, Ni, Cu, Zn, Ag, Sn, etc. For example, silicon-carbon composite material (Si-C) is an example of a composite.
[0036] The average inter-particle distance L of the negative electrode active material 1 is, for example, not less than 3.0 μm and not more than 4.5 μm. The average inter-particle distance L can be measured using a scanning electron microscope (SEM). In order to obtain the average inter-particle distance L, firstly, a three-dimensional measurement is performed on a SEM image magnified 1000 times or more and 1500 times. Then, in each of the three dimensions, the distances between the geometric centers of adjacent negative electrode active materials 1 are measured at 50 points. Then, the average inter-particle distance of the total 150 points measured is averaged, so that the average inter-particle distance L can be obtained.
[0037] The average particle size of the negative electrode active material 1 is, for example, 0.1 μm to 10 μm, preferably 0.5 μm to 8 μm, and more preferably 1 μm to 7 μm. The average particle size of the negative electrode active material 1 is obtained by taking the average value of the particle sizes of 150 points measured by a scanning microscope in the same manner as the method for measuring the average interparticle distance L of the negative electrode active material 1.
[0038] The fibrous material 2 is a linear particle with shape anisotropy. The fibrous material 2, for example, includes one or more selected from titanium oxide, potassium titanate, aluminum oxide, silicon carbide, silicon nitride, and silicon oxide. The fibrous material 2, for example, includes a material different from the negative electrode active material 1. Since silicon-based materials expand and contract in the same manner as the negative electrode active material 1, the fibrous material 2 preferably includes one or more selected from titanium oxide, potassium titanate, and aluminum oxide.
[0039] The fiber length of the fibrous substance 2 is, for example, not less than 20 μm and not more than 150 μm. The fiber length of the fibrous substance 2 can be obtained in the following order. First, the lithium-ion secondary battery 100 is disassembled and the negative electrode 30 is taken out. Next, the negative electrode 30 is immersed in a solvent capable of dissolving the binder constituting the negative electrode active material layer 34 for 1 hour. For example, when the binder is a polyimide resin, e SOLVE 21KZE-100 manufactured by KANEKO CHEMICAL CO., LTD. is used. Then, the solvent is filtered and washed several times to dry the powder remaining on the filter paper. The dried powder contains a negative electrode active material 1, a fibrous substance 2, and a conductive aid 3. By performing mapping using energy dispersive X-ray spectroscopy (EDS), the fibrous substance 2 can be determined from the powder. Moreover, using a scanning electron microscope, the size of the determined fibrous substance 2 is measured. The size of the fibrous material 2 is determined as the average value of 150 points measured with a scanning microscope, similarly to the average inter-particle distance L.
[0040] In addition, when the particle size distribution of the dried powder particles is measured using a particle size distribution measuring device (for example, manufactured by Malvern Panalytical), the particle size distribution of the dried powder can be obtained. The particle size distribution of the dried powder has two or more peaks. One of the peaks is a peak caused by the fibrous substance 2, which is generated near the fiber length of the fibrous substance 2. In addition, another peak is a peak caused by the negative electrode active material 1, which is generated near the particle size of the negative electrode active material 1. Because the particle size of the negative electrode active material 1 is different from the particle size of the fibrous substance 2, multiple peaks are generated in the particle size distribution of the powder. In the case where both the fibrous substance 2 and the negative electrode active material 1 contain silicon, the presence or absence of the fibrous substance 2 can be confirmed by measuring the particle size distribution of the powder.
[0041] The fibrous material 2 preferably accounts for 20% or less of the mass ratio of the entire negative electrode active material layer 34 . In addition, the fibrous material 2 preferably accounts for 1% or more of the mass ratio of the entire negative electrode active material layer 34 .
[0042] The thickness t of the negative electrode active material layer 34 (see Figure 1 ) is, for example, 8 μm or more and 150 μm or less. The value obtained by dividing the layer thickness t of the negative electrode active material layer 34 by the fiber length of the fibrous material 2 is, for example, 0.4 or more and 1.0 or less. When the fiber length of the fibrous material 2 is sufficient relative to the layer thickness t of the negative electrode active material layer 34, the fibrous material 2 acts as a skeleton of the negative electrode active material layer 34, and can suppress the cracking of the negative electrode active material layer 34 during charge and discharge.
[0043] The conductive additive 3 and the binder can use the same materials as those of the positive electrode 20. The binder in the negative electrode 30 may be, in addition to the materials listed in the positive electrode 20, cellulose, styrene-butadiene rubber, ethylene-propylene rubber, polyimide resin, polyamide-imide resin, acrylic resin, etc. Cellulose may be, for example, carboxymethyl cellulose (CMC).
[0044] <Diaphragm> The separator 10 is sandwiched between the positive electrode 20 and the negative electrode 30. The separator 10 isolates the positive electrode 20 and the negative electrode 30 to prevent a short circuit between the positive electrode 20 and the negative electrode 30. The separator 10 extends in a plane along the positive electrode 20 and the negative electrode 30. Lithium ions can pass through the separator 10.
[0045] The diaphragm 10 has, for example, an electrically insulating porous structure. The diaphragm 10 is, for example, a single layer or a laminate of a polyolefin film. The diaphragm 10 may also be a stretched film of a mixture of polyethylene, polypropylene, etc. The diaphragm 10 may also be a fiber nonwoven fabric formed of at least one constituent material selected from cellulose, polyester, polyacrylonitrile, polyamide, polyethylene, and polypropylene. The diaphragm 10 may also be, for example, a solid electrolyte. Solid electrolytes are, for example, polymer solid electrolytes, oxide solid electrolytes, and sulfide solid electrolytes. The diaphragm 10 may also be an inorganic coating diaphragm. The inorganic coating diaphragm is obtained by coating the surface of the above-mentioned film with a mixture of resins such as PVDF and CMC and inorganic substances such as alumina and silica. The inorganic coating diaphragm has excellent heat resistance and can inhibit the precipitation of transition metals dissolved from the positive electrode to the surface of the negative electrode.
[0046] <Electrolyte> The electrolyte is sealed in the outer casing 50 and impregnated in the power generation element 40. The electrolyte is not limited to a liquid electrolyte, and may be a solid electrolyte. The non-aqueous electrolyte includes, for example, a non-aqueous solvent and an electrolytic salt. The electrolytic salt is dissolved in the non-aqueous solvent.
[0047] The solvent is not particularly limited as long as it is a solvent commonly used in lithium-ion secondary batteries. The solvent includes, for example, any one of a cyclic carbonate compound, a chain carbonate compound, a cyclic ester compound, and a chain ester compound. The solvent may contain them mixed in any proportion. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate, vinylene carbonate, etc. Examples of chain carbonate compounds are diethyl carbonate (DEC), ethyl methyl carbonate (EMC), etc. Examples of cyclic ester compounds are γ-butyrolactone, etc. Examples of chain ester compounds are propyl propionate, ethyl propionate, ethyl acetate, etc.
[0048] The electrolytic salt is, for example, a lithium salt. The electrolyte is, for example, LiPF6, LiClO4, LiBF4, LiCF3SO3, LiCF3CF2SO3, LiC(CF3SO2)3, LiN(CF3SO2)2, LiN(CF3CF2SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(CF3CF2CO)2, LiBOB, LiN(FSO2)2, etc. As for the lithium salt, one kind may be used alone, or two or more kinds may be used in combination. From the viewpoint of the degree of ionization, the electrolyte preferably contains LiPF6. The degree of dissociation of the electrolytic salt at room temperature in the carbonate solvent is preferably 10% or more.
[0049] The electrolyte is preferably a solution in which LiPF6 is dissolved in a carbonate solvent. The concentration of LiPF6 is, for example, 1 mol / L. When the polyimide resin contains more aromatics, the polyimide resin sometimes exhibits charging behavior like soft carbon. When the electrolyte is a carbonate electrolyte solvent containing cyclic carbonate, lithium and polyimide can be uniformly reacted. In this case, the cyclic carbonate is preferably ethylene carbonate, fluoroethylene carbonate, and vinylene carbonate.
[0050] <Exterior body> The outer casing 50 seals the power generation element 40 and the non-aqueous electrolyte in its interior. The outer casing 50 can suppress leakage of the non-aqueous electrolyte to the outside and intrusion of moisture etc. from the outside into the lithium ion secondary battery 100.
[0051] like Figure 1 As shown, the outer package 50 includes, for example, a metal foil 52 and a resin layer 54 laminated on each surface of the metal foil 52. The outer package 50 is a metal laminate film in which the metal foil 52 is coated with a polymer film (resin layer 54) from both sides.
[0052] As the metal foil 52, for example, aluminum foil can be used. As the resin layer 54, a polymer film such as polypropylene can be used. The materials constituting the resin layer 54 on the inner side and the outer side can be different materials. For example, a polymer having a high melting point such as polyethylene terephthalate (PET) and polyamide (PA) can be used as the material of the outer side, and polyethylene (PE) and polypropylene (PP) can be used as the material of the polymer film on the inner side.
[0053] <Terminal> Terminals 60 and 62 are connected to the positive electrode 20 and the negative electrode 30, respectively. The terminal 60 connected to the positive electrode 20 is a positive terminal, and the terminal 62 connected to the negative electrode 30 is a negative terminal. The terminals 60 and 62 are used for electrical connection with the outside. The terminals 60 and 62 are formed of conductive materials such as aluminum, nickel, and copper. The connection method can be welding or screw fixing. In order to prevent short circuit, it is preferred to protect the terminals 60 and 62 with insulating tape.
[0054] The negative electrode 30, the positive electrode 20, the separator 10, the electrolyte solution, and the outer casing 50 are prepared separately, and these are assembled to produce the lithium ion secondary battery 100. An example of a method for producing the lithium ion secondary battery 100 will be described below.
[0055] For example, the negative electrode 30 is produced by sequentially performing a slurry preparation step, an electrode coating step, a drying step, and a rolling step.
[0056] The slurry preparation step is a step of mixing the negative electrode active material 1, the fibrous material 2, the conductive aid 3, the binder and the solvent to prepare a slurry. When a dispersion stabilizer is added to the slurry, the aggregation of the negative electrode active material can be suppressed. The solvent is, for example, water, N-methyl-2-pyrrolidone, etc.
[0057] The electrode coating process is a process of coating the slurry on the surface of the negative electrode current collector 32. There is no particular limitation on the method for coating the slurry. For example, a slot-die coating method or a doctor blade method can be used as the slurry coating method. For example, the slurry is coated at room temperature.
[0058] The drying step is a step of removing the solvent from the slurry. For example, the negative electrode current collector 32 coated with the slurry is dried in an atmosphere of 80°C to 350°C.
[0059] The rolling process is a process performed as needed. The rolling process is a process of applying pressure to the negative electrode active material layer 34 to adjust the density of the negative electrode active material layer 34. The rolling process is performed, for example, using a roll press device. By performing the rolling process, the thickness of the negative electrode active material layer 34 can be adjusted.
[0060] The positive electrode 20 can be produced in the same procedure as the negative electrode 30. As the separator 10 and the outer casing 50, commercially available separators and outer casings can be used.
[0061] Next, the positive electrode 20 and the negative electrode 30 are stacked with the separator 10 positioned therebetween to produce the power generating element 40. When the power generating element 40 is a wound body, the positive electrode 20, the negative electrode 30, and the separator 10 are wound around one end thereof.
[0062] Finally, the power generation element 40 is sealed in the outer body 50. The non-aqueous electrolyte is injected into the outer body 50. After the non-aqueous electrolyte is injected, the non-aqueous electrolyte is infiltrated into the power generation element 40. The outer body 50 is sealed by heating, etc., so that the lithium ion secondary battery 100 can be obtained. In addition, instead of injecting the electrolyte into the outer body 50, the power generation element 40 can be immersed in the electrolyte. After the power generation element is injected, it is preferably left to stand for 24 hours.
[0063] The lithium ion secondary battery 100 of the first embodiment has a fibrous substance 2 in the negative electrode active material layer 34, so the charge and discharge characteristics are not easily deteriorated. It is believed that this is because the fibrous substance 2 acts as the skeleton of the negative electrode active material layer 34, preventing the negative electrode active material layer 34 from cracking during charge and discharge. The cracking of the negative electrode active material layer 34 will cut off the conductive path in the negative electrode active material layer 34. By making the negative electrode active material layer 34 not easy to crack, the conductive path in the negative electrode active material layer 34 can be maintained, and the charge and discharge characteristics of the lithium ion secondary battery 100 are not easily deteriorated.
[0064] The embodiments of the present invention have been described in detail above with reference to the drawings, but the various structures and combinations of the various embodiments are merely examples, and additions, omissions, substitutions, and other changes to the structures may be made without departing from the spirit of the present invention. Example
[0065] Example 1 The positive electrode slurry is applied on one surface of an aluminum foil having a thickness of 15 μm. The positive electrode slurry is prepared by mixing a positive electrode active material, a conductive auxiliary agent, a binder, and a solvent.
[0066] The positive electrode active material uses Li x CoO2. Acetylene black was used as a conductive aid. Polyvinylidene fluoride (PVDF) was used as a binder. N-methyl-2-pyrrolidone was used as a solvent. 97 parts by mass of a positive electrode active material, 1 part by mass of a conductive aid, 2 parts by mass of a binder and 70 parts by mass of a solvent were mixed to prepare a positive electrode slurry. The amount of positive electrode active material in the dried positive electrode active material layer was 25 mg / cm 2 The solvent in the positive electrode slurry was removed in a drying furnace to produce a positive electrode active material layer. The positive electrode was produced by pressurizing the positive electrode active material layer with a roll press.
[0067] Next, negative electrode slurry was applied on one surface of a copper foil having a thickness of 10 μm. The negative electrode slurry was prepared by mixing a negative electrode active material, needle-shaped particles, a conductive auxiliary agent, a binder, and a solvent.
[0068] Silicon particles were used as the negative electrode active material. The average particle size of the silicon particles was 3.0 μm. Titanium oxide was used as the fibrous material. The fiber length of the fibrous material used was 20 μm. Carbon black was used as the conductive aid. Polyimide resin was used as the binder. N-methyl-2-pyrrolidone was used as the solvent. 78 parts by mass of silicon particles, 2 parts by mass of fibrous material, 5 parts by mass of conductive aid and 15 parts by mass of binder were mixed in N-methyl-2-pyrrolidone to prepare a negative electrode slurry. The negative electrode active material loading in the negative electrode active material layer after drying was 1.5 mg / cm2 The negative electrode active material layer was pressed by roll pressing and then fired at a temperature of 300° C. or higher for 5 hours in a nitrogen atmosphere. The thickness of the negative electrode active material layer after firing was 8 μm.
[0069] Next, an electrolyte was prepared. The composition of the electrolyte solvent was fluoroethylene carbonate (FEC): ethylene carbonate (EC): diethyl carbonate (DEC) = 10 volume %: 20 volume %: 70 volume %. In addition, output-enhancing additives, gas-suppressing additives, cycle characteristics-improving additives, safety performance-improving additives, etc. were added to the electrolyte. LiPF6 was used as the electrolytic salt. The concentration of LiPF6 was 1 mol / L.
[0070] (Preparation of lithium-ion secondary battery for evaluation) The negative electrode and the positive electrode obtained are stacked in a manner that the positive electrode active material layer and the negative electrode active material layer are opposite to each other through a diaphragm (porous polyethylene sheet) to obtain a laminate. The laminate is inserted into the outer body of the aluminum laminate film and heat-sealed except for one place around it, thereby forming a closed portion. Finally, after the above-mentioned electrolyte is injected into the outer body, a vacuum sealer is used to seal the remaining one place while decompressing it by heat sealing, thereby producing a lithium ion secondary battery. The manufactured lithium ion secondary battery is left to stand for 24 hours.
[0071] (Measurement of capacity maintenance after 100 cycles) The cycle characteristics of the lithium ion secondary battery were measured. The cycle characteristics were measured using a secondary battery charge and discharge tester (manufactured by Hokuto Denko Corporation).
[0072] The battery was charged at a constant current charging rate of 0.5C (the current value at which charging is completed in 1 hour at 25°C) until the battery voltage reached 4.2V, and discharged at a constant current discharging rate of 1.0C until the battery voltage reached 2.5V. The discharge capacity after the charge and discharge was detected, and the battery capacity Q1 before the cycle test was obtained.
[0073] For the battery whose battery capacity Q1 was obtained as described above, the secondary battery charge and discharge test device was used again to charge the battery at a constant current charging method with a charging rate of 0.5C until the battery voltage reached 4.2V, and to discharge the battery at a constant current discharge method with a discharge rate of 0.5C until the battery voltage reached 2.5V. The above charge and discharge were counted as 1 cycle, and 100 cycles of charge and discharge were performed. Afterwards, the discharge capacity after 100 cycles of charge and discharge was detected, and the battery capacity Q2 after 100 cycles was obtained.
[0074] The capacity retention rate after 100 cycles was determined from the capacities Q1 and Q2 determined as described above. The capacity retention rate E was determined by E=Q2 / Q1×100. The capacity retention rate of Example 1 was 90%.
[0075] The lithium-ion secondary battery after charge and discharge was disassembled, and the change rate of the thickness of the negative electrode active material layer was obtained. The change rate of the thickness of the negative electrode active material layer is calculated by "(thickness after charge)-(thickness after discharge)" / (thickness after discharge)×100. The change rate of Example 1 is 55%. In addition, the cross-section of the disassembled negative electrode active material layer was measured to obtain the distance between the negative electrode active materials. The average inter-particle distance between the negative electrode active materials in Example 1 is 2.9μm.
[0076] Examples 2 to 44, Comparative Examples 1 to 16 The difference between Examples 2 to 44 and Comparative Examples 1 to 16 and Example 1 is that any one of the characteristics of the type of material constituting the fibrous material, the fiber length of the fibrous material, the thickness of the negative electrode active material layer, and the average interparticle distance between the negative electrode active materials was changed. The changes are summarized in Tables 1 to 3. The other conditions were the same as those in Example 1, and the capacity retention rate of Examples 2 to 44 and Comparative Examples 1 to 16 was measured.
[0077] [Table 1]
[0078] [Table 2]
[0079] [Table 3]
[0080] The capacity retention rates of the lithium ion secondary batteries of Examples 1 to 44 were all higher than those of the lithium ion secondary batteries of Comparative Examples 1 to 16.
[0081] The capacity retention rates of Comparative Examples 1 to 4 and Comparative Examples 13 to 16 using carbon fibers were lower than those of the lithium ion secondary batteries of Examples 1 to 44. This is probably because carbon fibers are softer than inorganic materials such as ceramics and could not sufficiently reinforce the negative electrode active material layer 34 .
[0082] The capacity retention rates of Comparative Examples 5 to 8 using Cu whiskers were lower than those of the lithium ion secondary batteries of Examples 1 to 44. This is probably because metal materials are ductile and easily extend, and slip easily occurs in the crystal structure, so the effect of reinforcing the negative electrode active material layer 34 was not sufficiently obtained.
[0083] The capacity retention rates of Comparative Examples 9 to 12 in which the fibrous material had inappropriate size were lower than those of the lithium ion secondary batteries of Examples 1 to 44. This is considered to be because the fibrous material did not fully function as a skeleton for reinforcing the negative electrode active material layer 34 . Description of Reference Numerals
[0084] 1 Negative electrode active material 2Fibrous substances 3. Conductive additives 10 Diaphragm 20 positive electrode 22Positive electrode collector 24 Positive electrode active material layer 30 negative electrode 32 Negative electrode collector 34 Negative electrode active material layer 40 Power generation elements 50 outer body 52 metal foil 54 resin layer 60, 62 terminals 100 lithium-ion secondary batteries.
Claims
1. A negative electrode active material layer, wherein: Contains negative electrode active material and fibrous material, The negative electrode active material comprises silicon, The fibrous material comprises one or more selected from titanium oxide, potassium titanate, aluminum oxide, silicon carbide, silicon nitride and silicon oxide, The fiber length of the fibrous material is not less than 20 μm and not more than 150 μm, The value obtained by dividing the layer thickness by the fiber length is 0.4 or more and 1.0 or less.
2. The negative electrode active material layer according to claim 1, wherein The average inter-particle distance of the negative electrode active material is 3.0 μm or more and 4.5 μm or less.
3. The negative electrode active material layer according to claim 1, wherein The fibrous substance includes one or more selected from the group consisting of titanium oxide, potassium titanate, and aluminum oxide.
4. A negative electrode, wherein The negative electrode active material layer according to claim 1 is included.
5. A lithium ion secondary battery, wherein: have: The negative electrode according to claim 4; a positive electrode opposite to the negative electrode; and An electrolyte connects the negative electrode and the positive electrode.
